The gastroprotective effect of obestatin on indomethacin-induced acute ulcer is mediated by a vagovagal mechanism - YEGEN, BERRAK; YEGEN, ŞEVKET CUMHUR; ÖZDEMİR KUMRAL, ZARİFE NİGAR (AKADEMIAI KIADO ZRT, 2020)
In order to investigate the role of the vagus nerve in the possible gastroprotective effect of obestatin on the indomethacin-induced acute oxidative gastric injury, Sprague-Dawley rats of both sexes were injected subcutaneously with indomethacin (25 mg/kg, 5% NaHCO3) followed by obestatin (10, 30 or 100 mu g/kg). In other sets of rats, surgical vagotomy (Vx) or selective degeneration of vagal afferent fibers by perivagal capsaicin was performed before the injections of indomethacin or indomethacin + obestatin (30 mu g/kg). Gastric serosal blood flow was measured, and 4 h after ulcer induction gastric tissue samples were taken for histological and biochemical assays. Obestatin reduced the severity of indomethacin-induced acute ulcer via the reversal of reactive hyperemia, by inhibiting ulcer-induced neutrophil infiltration and lipid peroxidation along with the replenishment of glutathione (GSH) stores, whereas Vx abolished the inhibitory effect of obestatin on blood flow and lipid peroxidation, and worsened the severity of ulcer. On the other hand, serosal blood flow was even amplified by the selective denervation of the capsaicin-sensitive vagal afferent fibers, but obestatin-induced reduction in ulcer severity was not altered. In conclusion, the gastroprotective effect of obestatin on indomethacin-induced ulcer appears to involve the activation of the vagovagal pathway.
Keywords: NSAID; obestatin; vagus; neutrophil; capsaicin; hyperemia; indomethacin; GASTRIC-MUCOSAL INJURY; BLOOD-FLOW; VAGUS NERVE; GHRELIN; DAMAGE; RATS; ACTIVATION; PATHOGENESIS; INFLAMMATION; PROTECTS